THE IMPACT OF CORPORATE GOVERNANCE, PROFITABILITY AND LIQUIDITY ON DIVIDEND POLICY IN NON-CYCLICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Bonal, Emilie Monique; Santioso, Linda (International Journal of Application on Economics and Business, 2025)
This study aims to empirically analyze the effect of board size, board independence, profitability, and liquidity on dividend policy in non-cyclical segment companies published on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The research utilized 90 valid data points obtained from 30 non-cyclical companies as the research sample. The sampling method employed purposive sampling technique. Hypothesis testing was conducted using multiple linear regression, with data processing carried out using E-Views version 12 software. The appropriate model for this multiple linear regression analysis is the Fixed Effect Model (FEM). This study uses Dividend Payout Ratio (DPR) as a parameter to measure the company's dividend policy. The finding of the data processing indicate that board size and board independence have a crucial good influence on dividend policy, while profitability and liquidity do not have a crucial effect on dividend policy.